Exploring the Relationship Between Operations Management Practices and Students’ Satisfaction in the Canteen at Mabolo National High School - Medina, April Princess; Aguilon, Shaira Mae; Pepito, Crisa Mae B.; Enopequez, Avegail M.; Polinar, Mark Anthony N.; Rabanes, Bertella G.; Mahipos, April Marie (Future Science / FSH-PH Publications, 2024)
This descriptive-correlational study scrutinized the operations management and senior high school students’ satisfaction with the canteen inside the Mabolo National High School. Also, the relationship between the two variables was explored. Four hundred eighty-nine (489) respondents were chosen conveniently to participate in the data gathering using a modified tool validated by the experts and obtained 0.7346 internal consistency. Weighted mean and Pearson correlation coefficient were employed to analyze the data and yield valuable findings. Findings unveiled that students were satisfied with the personnel's treatment, the proactive approach of the canteen to provide fresh and healthy products, the products being served, and the processes of the canteen to maintain a quality service. Also, the study found that the operations management practices of the canteen have a significant relationship to the students’ satisfaction. Improving operations management is critical in meeting customer needs and leading to satisfaction. Consequently, maintaining and enhancing customer satisfaction can be attained by ensuring that the quality of products, processes, employees, and proactive measures is exceptional. Furthermore, future researchers can pursue other variables, such as canteen facilities, food prices, food tastes, and food preferences, for future studies as they might influence overall customer satisfaction.